Climate‐Driven Changes in Dissolved Organic Carbon and Water Clarity in Arctic Lakes of West Greenland. Issue 2 (18th February 2020) - Fowler, Rachel A.; Osburn, Christopher L.; Saros, Jasmine E.
Abstract: To assess climate‐mediated terrestrial‐aquatic linkages in Arctic lakes and potential impacts on light attenuation and carbon cycling, we evaluated lake responses to climate drivers in two areas of west Greenland with differing climate patterns. We selected four lakes in a warmer, drier area to compare with four lakes from a cooler, wetter area proximal to the Greenland Ice Sheet. In June from 2013–2018, we measured epilimnetic water temperature, 1% depth of photosynthetically active radiation (PAR), dissolved organic carbon (DOC), specific ultraviolet absorbance (SUVA254 ), DOC‐normalized absorbance at 380 nm ( a *380 ), and chlorophyll a . Interannual coherence of 1% PAR and DOC was particularly high for lakes within the warmer, drier area. This coherence suggests forcing of Arctic lake features by a large‐scale driver, likely climate. Redundancy analysis showed that monthly average precipitation, winter North Atlantic Oscillation (NAO) index (NAOW ), spring average air temperature, and spring average precipitation influenced the lake variables ( p = 0.003, adj. R 2 = 0.58). In particular, monthly average precipitation contributed to increases in soil‐derived DOC quality metrics and chlorophyll a and decreased 1% PAR. Interannual changes in lake responses to climate drivers were more apparent in the warmer, drier area than the cooler, wetter area. The interannual lake responses within and between areas, associated with climate trends, suggest that with ongoing rapid climate change in the Arctic, there could be widespread impacts on key lake responses important for light attenuation and carbon cycling. Plain Language Summary: Arctic lakes are particularly vulnerable to rapid climate change. To assess how climate factors influence lake characteristics important for water clarity and carbon cycling, we measured responses of lake variables to climate in two sets of lakes in west Greenland with different climate characteristics—a warmer, drier area and a cooler, wetter area. We found evidence that the lakes are responding similarly to climate factors, especially in the warmer, drier area. High ratios of lake surface area to depth and catchment to lake area, as well as lower inputs of precipitation may be responsible for these patterns of lake variable responses in the warmer, drier area. Mean annual precipitation was a primary control of soil‐derived carbon inputs and water clarity in the lakes. These findings suggest that with ongoing climate change in the Arctic, there could be widespread impacts on key controls of lake ecology and carbon cycling. Key Points: Dissolved organic carbon and water clarity in Arctic lakes are responsive to climate forcing Arctic lakes with limited hydrological connectivity exhibit coherent responses to climate forcing Lake responses are more coherent in lakes with greater surface area: mean depth and catchment: lake area and lower precipitation inputs